Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fmicb.2022.934857
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Bioactive Compounds, Antibacterial Activity, and Action Mechanism of Spore Powder From Aspergillus niger xj

Abstract: Aspergillus fungi can produce a wide range of secondary metabolites, and they have represented a potential resource of novel bioactive compounds. Bacterial plant diseases have a serious impact on the sustainable development of agriculture worldwide, so it is necessary to use natural antibacterial compounds in microorganisms to control plant pathogens. This study was conducted to investigate the bioactive compounds of Aspergillus niger xj, three plant pathogens (Agrobacterium tumefaciens T-37, Erwinia carotovor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…DWF5 (HYE68_001781), CYP51 (HYE68_002214), and cycloeucalenol cycloisomerase (HYE68_005067), which are involved in steroid synthesis, were significantly downregulated. The cell membrane plays an important role in the transport of osmoprotective compounds ( Liu et al, 2018 ), and an increase in cell membrane permeability causes the leakage of intracellular substances and an increase in electrical conductivity, leading to cell death ( Furuya et al, 2011 ; Wei et al, 2022 ). The present study demonstrated that the electrical conductivity of the Fp fermentation broth was significantly higher after TM28 treatment compared to the control ( Figure 3A ), suggesting that the metabolites produced by TM28 affected the membrane permeability of Fp .…”
Section: Discussionmentioning
confidence: 99%
“…DWF5 (HYE68_001781), CYP51 (HYE68_002214), and cycloeucalenol cycloisomerase (HYE68_005067), which are involved in steroid synthesis, were significantly downregulated. The cell membrane plays an important role in the transport of osmoprotective compounds ( Liu et al, 2018 ), and an increase in cell membrane permeability causes the leakage of intracellular substances and an increase in electrical conductivity, leading to cell death ( Furuya et al, 2011 ; Wei et al, 2022 ). The present study demonstrated that the electrical conductivity of the Fp fermentation broth was significantly higher after TM28 treatment compared to the control ( Figure 3A ), suggesting that the metabolites produced by TM28 affected the membrane permeability of Fp .…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxyl and carbonyl groups contained in the compound cause antioxidant and antibacterial activity. [61][62][63] The ethyl acetate extract of A. niger showed very strong antioxidant activity with an IC50 value close to ascorbic acid (IC50 < 20 µg/mL). Its antibacterial activity is in the strong category against the four test bacteria.…”
Section: Molecular Identification Of Endophytic Fungimentioning
confidence: 99%
“…Among these compounds, 47 has exhibited antibacterial activity against Ralstonia solanacearum RS-2, with an MIC value of 15.56 μg/mL. SEM, assessment of the cell membrane permeability, and SDS-PAGE analysis have determined that the mechanism of action of 47 involves the inhibition of bacterial protein synthesis and intracellular metabolism [ 90 ].…”
Section: Antimicrobial Effects and Mechanisms Of Action Of Natural Co...mentioning
confidence: 99%
“…The endophytic fungus Pestalotia sp., isolated from the leaves of Heritiera fomes, has yielded two compounds: oxysporone (89) and xylitol (90). These compounds demonstrate antibacterial activities against various strains of methicillin-resistant S. aureus, including ATCC 25923, SA-1199B, RN4220, XU212, EMRSA-15, and EMRSA-16.…”
Section: Biosynthetic Gene Clusters Of Secondary Metabolites Of Endop...mentioning
confidence: 99%